2018
DOI: 10.1186/s12885-018-4491-6
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA; a novel biomarker predicting recurrence free survival of breast cancer patients receiving adjuvant therapy

Abstract: BackgroundThis study was carried out to evaluate the prognostic value of KIBRA in breast cancer.MethodsThis retrospective study included breast cancer patients who sought the services of the immunohistochemistry laboratory of our unit from 2006 to 2015. Tissue microarrays were constructed and immunohistochemical staining was done to assess the KIBRA expression. The Kaplan-Meier model for univariate and Cox-regression model with backward stepwise factor retention method for multivariate analyses were used. Chi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…While WWC1 has been primarily linked to episodic memory and Alzheimer's disease, a recent candidate gene study observed an association between WWC1 variants and risk of estrogen‐receptor positive breast cancer in women of African ancestry. Likewise, WWC1/KIBRA has been linked to breast cancer outcomes, including recurrence‐free survival and metastasis . In the current study, we found an association with ER negative breast cancer for the SNP nearest to the WWC1 gene.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…While WWC1 has been primarily linked to episodic memory and Alzheimer's disease, a recent candidate gene study observed an association between WWC1 variants and risk of estrogen‐receptor positive breast cancer in women of African ancestry. Likewise, WWC1/KIBRA has been linked to breast cancer outcomes, including recurrence‐free survival and metastasis . In the current study, we found an association with ER negative breast cancer for the SNP nearest to the WWC1 gene.…”
Section: Discussionsupporting
confidence: 60%
“…Likewise, WWC1/KIBRA has been linked to breast cancer outcomes, including recurrence-free survival and metastasis. 32,33 In the current study, we found an association with ER negative breast cancer for the SNP nearest to the WWC1 gene. To our knowledge, the other two loci associated with EOC in women of African descent at the suggestive threshold, LOC101927394 and UGT2A2, have not been reported in association with cancer or other diseases.…”
Section: Discussionsupporting
confidence: 57%
“…The third most significant master regulator, the WW and C2 domain-containing 1 ( WWC1 ) gene, produces a phosphoprotein. It has functions in restricting proliferation and promoting apoptosis, as well as in regulating transcription of estrogen receptor α ( ESR1 ) [ 82 ]. The WWC1 gene is part of the hippo pathway, which also regulates cell proliferation and apoptosis and plays a role in position sensing and lineage specification in preimplantation embryos [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we show that decreased KIBRA expression correlates with reduced BC patients’ OS and RFS. Notably, during the period our manuscript was under review, it was reported that luminal BC patients with endocrine therapy and KIBRA-low expression had an RFS disadvantage over those who were positive for KIBRA [ 39 ]. Accordingly, the correlation between expression of WWC2/WWC3 and clinical features of breast cancer must be further determined.…”
Section: Discussionmentioning
confidence: 99%